Controlling orbital moment and spin orientation in CoO layers by strain - Csiszár, Szilárd István; Haverkort, Maurits W. (Physical review letters, 2005)
We have observed that CoO films grown on different substrates show dramatic differences in their magnetic properties. Using polarization dependent x-ray absorption spectroscopy at the Co L2,3 edges, we revealed that the magnitude and orientation of the magnetic moments strongly depend on the strain in the films induced by the substrate. We presented a quantitative model to explain how strain together with the spin-orbit interaction determine the 3d orbital occupation, the magnetic anisotropy, as well as the spin and orbital contributions to the magnetic moments. Control over the sign and direction of the strain may, therefore, open new opportunities for applications in the field of exchange bias in multilayered magnetic films.
Gesehen am 08.11.2017